Arsenite oxidation and treatment by ultrasound/iron in aqueous solutions - Cui, M.; Jang, M.; Lee, S.; Kweon, B.; Yun, S.T.; Khim, J. (2011)
The oxidation and treatment of arsenite [As(III)] with ultrasound (US) and Fe(II) was investigated in aqueous solutions. The oxidation of As(III) into As(V), over 99.1%, was obtained by US450kHz. The kinetics of As(III) oxidation were interpreted using the modified pseudo-first-order kinetic model. The half life of As(III) was approximately 3.47 × 10-2 for the US450kHz/Fe(II)0:4mg/L reaction and depended on the iron concentration. The arsenic removal capacity of complexed and coprecipitated FeAsO4(s) was estimated to be 16.12mg per g of iron oxide. It is concluded that the sonochemical treatment of As(III) solution in the presence of Fe(II) is a simple and viable technique for the oxidation of As(III) into arsenate [As(V)] and the treatment of total arsenic. © 2011 The Japan Society of Applied Physics.